CD154‐expressing CMV‐specific T cells associate with freedom from DNAemia and may be protective in seronegative recipients after liver or intestine transplantation. (27th October 2019) - Ashokkumar, Chethan; Green, Michael; Soltys, Kyle; Michaels, Marian; Mazariegos, George; Reyes‐Mugica, Miguel; Higgs, Brandon W.; Spishock, Brianna; Zaccagnini, Madison; Sethi, Pradeep; Rzempoluch, Alexis; Kepler, Alexandra; et al.
Abstract: Cell‐mediated immunity to CMV, if known, could improve antiviral drug therapy in at‐risk children and young adults with LT and IT. Host immunity has been measured with CMV‐specific T cells, which express IFNγ, but not those which express CD154, a possible substitute for IFNγ. CMV‐specific CD154+ T cells and their subsets were measured with flow cytometry after stimulating PBL from recipient blood samples with an overlapping peptide mix of CMV‐pp65 antigen for up to 6 hours. CMV‐specific CD154+ T cells co‐expressed IFNγ in PBL from three healthy adults and averaged 3.8% (95% CI 3.2%‐4.4%) in 40 healthy adults. CMV‐specific T cells were significantly lower in 19 CMV DNAemic LT or IT recipients, compared with 126 non‐DNAemic recipients, 1.3% (95% CI 0.8‐1.7) vs 4.1 (95% CI 3.6‐4.6, P < .001). All T‐cell subsets demonstrated similar between‐group differences. In logistic regression analysis of 46 training set samples, 12 with DNAemia, all obtained between days 0 and 60 from transplant, CMV‐specific T‐cell frequencies ≥1.7% predicted freedom from DNAemia with NPV of 93%. Sensitivity, specificity, and PPV were 83%, 74%, and 53%, respectively. Test performance was replicated in 99 validation samples. In 32 of 46 training set samples, all from seronegative recipients, one of 19 recipients with CMV‐specific T‐cell frequencies ≥1.7% experienced DNAemia, compared with 8 of 13 recipients with frequencies <1.7% ( P = .001). CMV‐specific CD154+ T cells are associated with freedom from DNAemia after LT and IT. Among seronegative recipients, CMV‐specific T cells may protect against the development of CMV DNAemia.